SYNTHESIS OF STARCH-G-POLY(FUMARIC ACID) AND STARCH-G-POLY(POTASSIUM 3-SULFOPROPYL ACRYLATE) FOR PICKERING EMULSION STABILIZER APPLICATIONS - Irlizcha Felicia, Shaina
Emulsion currently plays an important role in various fields, such as cosmetics, food, and medicine. Thermodynamically, emulsion is unstable, so an emulsion stabilizer is needed. A Pickering emulsion is an emulsion stabilized by solid particles. One of the ingredients that can be used as a Pickering emulsion stabilizer is starch. However, starch has several disadvantages which limit its use as an emulsion stabilizer. Natural starch is generally hydrophilic and has many strong intramolecular and intermolecular bonds in the form of hydrogen bonds. Starch tends to form aggregates so it is difficult to dissolve in water. To increase its emulsification ability, starch must be modified by adding a new functional group. In this study, starch was isolated from cassava with a yield of 9.4% (w/w). Starch was modified by graft copolymerization method using fumaric acid and potassium 3-sulfopropyl acrylate as monomers. The synthesis of starch-g-poly(fumaric acid) was carried out by two methods (thermal and microwave) with two degrees of polymerization (DPn) of 20 and 60. The resulting products, starch-g-poly(fumaric acid) were yellowish-white solid with yields of 9.8–28.8% ( b/w). The FTIR spectra of the starch-g-poly(fumaric acid) copolymers showed loss of absorption -C=C-H at a wave number of 3080 cm-1. In addition, the absorption of -OH of the copolymer at a wave number of 3000 cm-1 looked sharper and narrower. XRD characterization showed that starch-g-poly(fumaric acid) was semi-crystalline with one peak at 2? 20.8º. The synthesis of starch-g-poly(potassium 3-sulfopropyl acrylate) was carried out with DPn of 20 and 60. Starch-g-poly(potassium 3-sulfopropyl acrylate) copolymers was successfully synthesized with yields of 13.4–23.6% and grafting percentages of 123.5%?254.6%. The starch-g-poly(potassium 3-sulfopropyl acrylate) FTIR spectra showed a new peak at 1700 cm-1 wave number which was the stretching vibration of C=O. In addition, the absorption intensity of -OH at a wave number of 3000 cm-1 was reduced compared to starch. XRD characterization showed that starch-g-poly(potassium 3-sulfopropyl acrylate) was crystalline with peaks at 2? 20º, 29º, and 41º. The stability test showed that the emulsions stabilized by starch-g-poly(potassium 3-sulfopropyl acrylate) was more stable against time, shock, dilution, and heating compared to emulsions stabilized by starch and starch-g-poly(fumaric acid). In addition, measurements of turbidity, PSA, and zeta potential showed that the ability of starch-g-poly(potassium 3-sulfopropyl acrylate) as an emulsion stabilizer was affected by pH. This indicated that pH could affect the charge of starch-g-poly(potassium 3-sulfopropyl acrylate). Changes in charge on starch-g-poly(potassium 3-sulfopropyl acrylate) could change the interaction of starch-g-poly(potassium 3-sulfopropyl acrylate) with water and oil, which led to the formation of coalescence.